Development of engineered cementitious composites (ECC) using artificial fine aggregates. (25th October 2021) - Xu, Ling-Yu; Huang, Bo-Tao; Dai, Jian-Guo
Highlights: ECC using artificial fine aggregates were developed for the first time. The developed high-strength ECC incorporating geopolymer and cement-bonded artificial fine aggregates achieved a compressive strength of 122.4 and 120.9 MPa, respectively. Among the existing ambient-cured high-strength ECC, the developed geopolymer aggregate ECC recorded the highest tensile strain capacity (9.0%). For high-strength ECC, the use of geopolymer artificial fine aggregate resulted in more saturated multiple cracking. Abstract: In this study, Engineered/Strain-Hardening Cementitious Composites (ECC/SHCC) using artificial fine aggregates [i.e., geopolymer aggregates (GPA) and cement-bonded aggregates (CBA)] were developed for the first time. The developed GPA-ECC and CBA-ECC showed a compressive strength over 120 MPa, and the GPA-ECC recorded the highest tensile strain capacity (9.0%) among the existing ambient-cured high-strength ECC in literature. Compared with fine silica sand ECC (FSS-ECC) as a control mix, GPA-ECC and CBA-ECC showed lower compressive and tensile strength, owing to their lower aggregate strengths. From digital image correlation analysis, a more saturated multiple cracking behavior was observed for GPA-ECC as compared to CBA-ECC and FSS-ECC. In addition, the use of artificial aggregates had marginal effect on the crack width distribution of high-strength ECC. The findings in this study demonstrate the feasibility of using artificial fine aggregates in ECC production and provide a new avenue to improve ductility and sustainability for ECC materials.